Ecosystem services supply by the soil of forest fragment in a highland humid enclave (Revista de Ciências Agroveterinárias, 2023)
The encroachment of agricultural activities on the remnants of the Atlantic Forest in the high altitudes of the Brazilian Northeast led to the formation of forest fragments that need to be better understood. To this end, research was conducted in a forest fragment of Mata do Pau-Ferro in a highland humid enclave, locally known as "Brejo Paraibano", to characterize the soil through chemical, physical, mineralogical, and geochemical attributes, to evaluate the potential of the soil in the provision of services environment. Ferralsols samples were collected and analyzed in a layer from 0 to 20 cm deep. The results showed that soil properties have a direct influence on the provision of ecosystem services, especially support, regulation, provision, and cultural services. Among the properties, essential nutrient content, carbon stock, minerals that can provide nutrients in the long term, texture, density, and organic matter content stand out, favoring water storage and adequate development of plant species.
Keywords: essential nutrients; territorial planning; nutrients; forests; soil characteristics; carbon